2010
DOI: 10.1016/j.devcel.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Kinase Directs Bazooka/Par-3 Planar Polarity during Drosophila Axis Elongation

Abstract: Summary Cell rearrangements shape the Drosophila embryo through spatially regulated changes in cell shape and adhesion. We show that Bazooka/Par-3 (Baz) is required for the planar polarized distribution of myosin II and adherens junction proteins and polarized intercalary behavior is disrupted in baz mutants. The myosin II activator Rho-kinase is asymmetrically enriched at anterior and posterior borders of intercalating cells in a pattern complementary to Baz. Loss of Rho-kinase results in expansion of the Baz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
262
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(288 citation statements)
references
References 64 publications
16
262
2
1
Order By: Relevance
“…As depletion of PIP3 did not block actomyosin cable assembly, loss of Baz must also trigger a PIP3-independent pathway that drives cable assembly. Baz exhibits a reciprocal distribution to actomyosin in other processes in the Drosophila embryo, including germband extension and amnioserosa remodelling; however, the molecular basis of this reciprocal relationship is not well understood, although recent work has indicated that Rho-kinase is involved (Pope and Harris, 2008;Simões et al, 2010;Zallen and Wieschaus, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As depletion of PIP3 did not block actomyosin cable assembly, loss of Baz must also trigger a PIP3-independent pathway that drives cable assembly. Baz exhibits a reciprocal distribution to actomyosin in other processes in the Drosophila embryo, including germband extension and amnioserosa remodelling; however, the molecular basis of this reciprocal relationship is not well understood, although recent work has indicated that Rho-kinase is involved (Pope and Harris, 2008;Simões et al, 2010;Zallen and Wieschaus, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Elongation is reduced in embryos deficient for myosin-II heavy chain, myosin regulatory light chain (MRLC), Rok, which activates MRLC, or Shroom (Bertet et al, 2004;Simões et al, 2010Simões et al, , 2014. Furthermore, disruption of Par-3, Par-6 or aPKC also impairs elongation (Blankenship et al, 2006;Simões et al, 2010;Zallen and Wieschaus, 2004), potentially due to roles for these proteins in rosette formation. In addition, microtubules are important for the asymmetric localization of a mobile E-cadherin pool and Par-3 complex (Bulgakova et al, 2013).…”
Section: Drosophila Epithelial Morphogenesismentioning
confidence: 99%
“…It is crucial for the processes of gastrulation, neurulation and organogenesis, all of which require multicellular rearrangements such as tissue elongation. In certain contexts, the planar polarized distribution of molecules involved in acto-myosin constriction and cell adhesion can give rise to rosette formation (Blankenship et al, 2006;Lienkamp et al, 2012;Simões et al, 2010;Tamada et al, 2012). In a subset of these cases, molecules involved in the planar cell polarity (PCP) pathway, including noncanonical Wnt, are clearly required for rosette formation (Lienkamp et al, 2012).…”
Section: Making Rosettes Via Planar Polarized Constrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1), whether intercalation per se is the driving force leading to branch extension remains debatable. Several studies in epithelial tissues suggest that intercalation is the direct consequence of increased cortical contractility resulting from the dynamics and the localization of MyoII, thereby generating the major force controlling tissue elongation (Bardet et al, 2013;Bertet et al, 2004;Rauzi et al, 2008;Simoes et al, 2010). However, external forces acting on tissue boundaries have also been implicated in tissue elongation.…”
Section: Introductionmentioning
confidence: 99%